Managers' Perception of Proper Ethical Conduct: The Effect of Sex, Age, and Level of Education - Deshpande, Satish P. (Journal of business ethics, 1997)
This study examined the impact of sex, age, and level of education on the perception of various business practices by managers of a large non-profit organization. Female managers perceived the acceptance of gifts and favors in exchange for preferential treatment significantly more unethical than male managers. Older managers (40 plus) perceived five practices significantly more unethical than younger managers (giving gifts/favors in exchange for preferential treatment, divulging confidential information, concealing ones error, falsifying reports, and calling in sick to take a day off). The practice of padding expense account by over 10% was reported to be significantly more unethical by managers with a graduate degree.